Geografia cultural: gênese, possibilidades e um pouco de música - Taoni, Lucas Jurado [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper addresses the Cultural Geography from the meeting of several authors, especially geographers, and development of the area from the Ratzel perspective. We demonstrate the most important concepts that give substance to this type of analysis, still very new in the country, as well as the specific way that cultural geographers see the space and articulate the cultural geographic content. Clearly it is not possible to account for neither all the developments of Cultural Geography nor the wide plurality of conjectures that this type of interface allows the geographical research. Therefore, the text comprises three essential parts. The first part deals with the genesis of thought in cultural geography and the problems surrounding this first practice. The second part deals with the renewal of the area during the 1970s and a set of concepts, authors and research possibilities that rework way to search in Geography cultural bias. Finally, the third part deals with the Geography and Music, Music Geography, as an example of sensitive renovation and expansion in the repertoire of objects of study that brings Cultural Geography. All this panoramically, but in an attempt to demonstrate the seriousness of this line of research in Geography, the suitability of the authors who started and wealth of detail that this amalgam produces

Este trabalho aborda a Geografia Cultural a partir da reunião de vários autores, especialmente geógrafos, e do desenvolvimento da área a partir da perspectiva ratzeliana. Buscamos demonstrar os conceitos mais importantes que dão substância a este tipo de análise, ainda muito recente no país, bem como a maneira específica que geógrafos culturais vêem o espaço e articulam o conteúdo geográfico ao cultural. É evidente que não é possível dar conta de todos os desdobramentos da Geografia Cultural e tampouco da ampla pluralidade de conjecturas que este tipo de interface permite na pesquisa geográfica. Por isso, o texto compreende três partes essenciais. A primeira parte aborda a gênese do pensamento cultural em geografia e os problemas adjacentes a esta prática primeira. A segunda parte trata da renovação da área no decorrer dos anos 1970 e um conjunto de conceitos, autores e possibilidades de pesquisa que repaginaram a maneira de pesquisar Geografia no viés cultural. Por fim, a terceira parte aborda a Geografia e Música, Music Geography, como exemplo da renovação e ampliação sensível no repertório de objetos de estudo que traz a Geografia Cultural. Tudo isso panoramicamente, mas na tentativa de demonstrar a seriedade desta linha na pesquisa de Geografia, a idoneidade dos autores que a iniciaram e a riqueza de detalhes que este amálgama produz
Keywords: Geografia humana; Música; Cultura